Antimicrobial resistance in commensal Escherichia coli from humans and chickens in the Mekong Delta of Vietnam is driven by antimicrobial usage and potential cross-species transmission. Issue 3 (27th May 2022) - Nhung, Nguyen Thi; Yen, Nguyen Thi Phuong; Dung, Nguyen Thi Thuy; Nhan, Nguyen Thi Minh; Phu, Doan Hoang; Kiet, Bach Tuan; Thwaites, Guy; Geskus, Ronald B.; Baker, Stephen; Carrique-Mas, Juan; Choisy, Marc
Abstract: Objectives: To investigate phenotypic antimicrobial resistance (AMR) in relation to antimicrobial use (AMU) and potential inter-species transmission among Escherichia coli from humans and chickens located in the same households in the Mekong Delta of Vietnam. Methods: We collected data on AMU and faecal swabs from humans ( N = 426) and chickens ( N = 237) from 237 small-scale farms. From each sample, one E. coli strain was isolated and tested for its susceptibility against 11 antimicrobials by Sensititre AST. The association between AMR and AMU was investigated by logistic regression modelling. Using randomization, we compared the degree of similarity in AMR patterns between human and chicken E. coli from the same farms compared with isolates from different farms. Results: The AMU rate was ∼19 times higher in chickens (291.1 per 1000 chicken-days) than in humans (15.1 per 1000 person-days). Isolates from chickens also displayed a higher prevalence of multidrug resistance (63.3%) than those of human origin (55.1%). AMU increased the probability of resistance in isolates from human (ORs between 2.1 and 5.3) and chicken (ORs between 1.9 and 4.8). E. coli from humans and chickens living on same farms had a higher degree of similarity in their AMR patterns than isolates from humans and chicken living on different farms. Conclusions: We demonstrated the co-influence of AMU and potential transmission on observed phenotypic AMR patterns among E. coli isolates from food-producing animals and in-contact humans. Restricting unnecessary AMU alongside limiting interspecies contact (i.e. increasing hygiene and biocontainment) are essential for reducing the burden of AMR.